Aportes da sociologia reflexiva para a compreensão do conceito jurídico de discriminação estrutural - Pinto, Rodrigo da Silva Vernes (Universidade do Vale do Rio dos Sinos, 2024)
In Brazilian law, even with a set of regulations alert to discrimination, certain structures of subordination such as structural racism, sexism, structural homotransphobia and other structural ethnic and aporophobic inequalities maintain discrimination persistently in social context. Studies about that subject-area are developed by the legal discipline of anti-discrimination law. It gathers answers to implement the principle of equality and define structural discrimination. Given the theoretical limitations for proposing its concept, which are restricted to descriptions and adjectives linked to terms such as “disadvantages”, “patterns” and “systematic processes of exclusion”, the objective of this thesis is to make use of the contributions of Pierre Bourdieu's reflexive sociology to propose an understanding of the phenomenon of structural discrimination and advance its legal concept. Specifically, the objective is to understand what structures society and domination, based on Bourdiesian categories, and to analyze how legal literature has faced the problem to ultimately relate reflexive sociology and Law; through the conception of what structures society and domination, a legal concept of structural discrimination is proposed. Through theoretical-descriptive methodology, the approach method used is hypothetical-deductive using historical, comparative and typological procedure methods, with the research divided into three parts. The first part addresses sociological concepts and categories for understanding what social structure and domination are, using Pierre Bourdieu's contributions in debate with other sociological studies on the subject, such as those from Max Weber, Émile Durkheim , Karl Marx and Michael Foucault. Other divergences are also addressed, such as those coming from the structuralist linguistics of Ferdinand Saussure and the structuralist anthropology of Lévi-Strauss to, in the end, after the critical exposition of Bourdieu's theoretical framework, demonstrate its reception in the legal field. The second part establishes a dialogue between sociological premises and legal studies on structural discrimination, exposing the potentialities and limitations in the theoretical confrontation on the topic; taking as a reference the studies related to structural racism and, on the other hand, more general understandings about the treatment given to structures of subordination, the construction of legislation in racial relations and the movements anti-racist social issues throughout history are addressed. Something that extends to other biases in the anti-discrimination struggle, such as structural discrimination based on gender and ethnicity, demonstrating the consequences arising from sexism, coloniality and homotransphobia. The third part presents the legal concept of structural discrimination based on reflexive sociology, relating it to its application in legal dogmatics and its repercussions on other antidiscriminatory legal categories such as direct, indirect and multiple discrimination, antisubordination, legislation anti-discrimination law and in jurisprudential precedents on structural disputes. The thesis argues that, based on reflexive sociology, the legal concept of structural discrimination can be defined by the set of historical relations that potentially cause and generate effects on individual and material structures internalized and externalized by social agents and groups. This results in effects of structural social domination/discrimination with the submission of those dominated/discriminated by power and symbolic violence, a concept capable of enabling transformative measures of discriminatory structural dominations.

En el derecho brasileño, incluso con un conjunto de normas atentas a la discriminación, ciertas estructuras de subordinación como el racismo estructural, el machismo estructural, la homotransfobia estructural y otras desigualdades estructurales étnicas y aporofóbicas mantienen la discriminación persistente en la vida social cotidiana. Los estudios sobre el tema son desarrollados por la disciplina jurídica del derecho antidiscriminatorio. El derecho antidiscriminatório reúne respuestas para implementar el principio de igualdad y definir la discriminación estructural. Dadas las limitaciones teóricas para proponer su concepto, que se restringen a descripciones y adjetivos vinculados a términos como “desventajas”, “patrones” y “procesos sistemáticos de exclusión”, el objetivo de esta tesis es aprovechar los aportes de la sociología reflexiva de Pierre Bourdieu para proponer una comprensión del fenómeno de la discriminación estructural y avanzar en su concepto jurídico. En concreto, el objetivo es comprender qué estructura la sociedad y la dominación, a partir de categorías bourdiesianas, y analizar cómo la literatura jurídica ha afrontado el problema para, en última instancia, relacionar la sociología reflexiva y el Derecho; a través de la concepción de lo que estructura la sociedad y la dominación, se propone un concepto jurídico de discriminación estructural. A través de una metodología teórico-descriptiva, el método de abordaje utilizado es hipotético-deductivo utilizando métodos históricos, comparativos y de procedimiento tipológico, dividiendo la investigación en tres partes. La primera parte aborda conceptos y categorías sociológicas para comprender qué es estructura social y dominación, utilizando los aportes de Pierre Bourdieu en debate con otros estudios sociológicos sobre el tema, como los de Max Weber, Émile Durkheim, Karl Marx y Michael Foucault. También se abordan otros contrapuntos, como los provenientes de la lingüística estructuralista de Ferdinand Saussure y la antropología estructuralista de Lévi-Strauss para, al final, tras la exposición crítica del marco teórico de Bourdieu, demostrar su recepción en el campo jurídico. La segunda parte establece un diálogo entre premisas sociológicas y estudios jurídicos sobre discriminación estructural, exponiendo las potencialidades y limitaciones en el enfrentamiento teórico sobre el tema; Tomando como referencia estudios relacionados con el racismo estructural y, por otro lado, comprensiones más generales sobre el tratamiento dado a las estructuras de subordinación, la construcción de legislación en las relaciones raciales y los movimientos sociales antirracistas a lo largo de la historia. Algo que se extiende a otros sesgos en la lucha contra la discriminación, como la discriminación estructural por razón de género y etnia, evidenciando las consecuencias derivadas del sexismo, la colonialidad y la homotransfobia. La tercera parte presenta el concepto jurídico de discriminación estructural desde la sociología reflexiva, relacionándolo con su aplicación en la dogmática jurídica y sus repercusiones en otras categorías jurídicas antidiscriminatorias como la discriminación directa, indirecta y múltiple, la antisubordinación, la legislación antidiscriminatoria y en precedentes jurisprudenciales sobre disputas estructurales. La tesis sostiene que, con base en la sociología reflexiva, el concepto jurídico de discriminación estructural puede definirse como el conjunto de relaciones históricas que potencialmente causan y generan efectos sobre estructuras individuales y materiales introyectadas y externalizadas por agentes y grupos sociales. Esto resulta en efectos de dominación/discriminación social estructural con el sometimiento de los dominados/discriminados por el poder y la violencia simbólica, concepto capaz de posibilitar medidas transformadoras de dominación estructural discriminatoria.
Keywords: Discriminação; Discriminação estrutural; Sociologia reflexiva; Pierre Bourdieu; Discrimination; Structural discrimination; Reflexive sociology; Discriminación; Discriminación estructural; Sociología reflexiva; ACCNPQ::Ciências Sociais Aplicadas::Direito